Targeted rapid knee MRI exam using T2 shuffling - Tamir, Jonathan I.; Taviani, Valentina; Alley, Marcus T.; Perkins, Becki C.; Hart, Lori; O'Brien, Kendall; Wishah, Fidaa; Sandberg, Jesse K; Anderson, Michael J.; Turek, Javier S.; Willke, Theodore L.; Lustig, Michael; et al. (Journal of magnetic resonance imaging, 2019)
Background MRI is commonly used to evaluate pediatric musculoskeletal pathologies, but same‐day/near‐term scheduling and short exams remain challenges. Purpose To investigate the feasibility of a targeted rapid pediatric knee MRI exam, with the goal of reducing cost and enabling same‐day MRI access. Study Type A cost effectiveness study done prospectively. Subjects Forty‐seven pediatric patients. Field Strength/Sequence 3T. The 10‐minute protocol was based on T2 Shuffling, a four‐dimensional acquisition and reconstruction of images with variable T2 contrast, and a T1 2D fast spin‐echo (FSE) sequence. A distributed, compressed sensing‐based reconstruction was implemented on a four‐node high‐performance compute cluster and integrated into the clinical workflow. Assessment In an Institutional Review Board‐approved study with informed consent/assent, we implemented a targeted pediatric knee MRI exam for assessing pediatric knee pain. Pediatric patients were subselected for the exam based on insurance plan and clinical indication. Over a 2‐year period, 47 subjects were recruited for the study and 49 MRIs were ordered. Date and time information was recorded for MRI referral, registration, and completion. Image quality was assessed from 0 (nondiagnostic) to 5 (outstanding) by two readers, and consensus was subsequently reached. Statistical Tests A Wilcoxon rank‐sum test assessed the null hypothesis that the targeted exam times compared with conventional knee exam times were unchanged. Results Of the 49 cases, 20 were completed on the same day as exam referral. Median time from registration to exam completion was 18.7 minutes. Median reconstruction time for T2 Shuffling was reduced from 18.9 minutes to 95 seconds using the distributed implementation. Technical fees charged for the targeted exam were one‐third that of the routine clinical knee exam. No subject had to return for additional imaging. Data Conclusion The targeted knee MRI exam is feasible and reduces the imaging time, cost, and barrier to same‐day MRI access for pediatric patients. Level of Evidence: 2 Technical Efficacy: Stage 6 J. Magn. Reson. Imaging 2019.